Comparative prospective study of Hysterosalpingography and hysteroscopy in infertile women - Leena Wadhwa; Pooja Rani; Pushpa Bhatia (Wolters Kluwer Medknow Publications, 2017)
Aim: To compare the findings and diagnostic accuracy of Hysterosalpingography (HSG) and hysteroscopy in infertile women. Setting and Design: Prospective comparative study in a tertiary care Centre. Material and Methods: 108 women with primary or secondary infertility were recruited. In all women after basic infertility workup, both HSG and hysteroscopy were performed. Results: Out of 108 women, in 3 women HSG couldn't be done and in one woman there was uterine perforation on hysteroscopy. HSG showed normal uterine cavity in 77.8% (81/105) women and abnormal in 22.85% (24/105). Hysteroscopy findings were normal in 70.09% (75/107) and abnormal in 29.91% (32/107). Hysteroscopy detected incidental findings in 15.38% (16/104) cases. HSG showed irregular uterine cavity in 14.15% (15/105) women but on hysteroscopy; normal cavity was present in 6 (40%) women and abnormality was detected in 9 (60%) women. The sensitivity, specificity, positive predictive and negative predictive value of HSG in evaluating uterine cavity abnormalities were 44.83% (95% confidence interval (CI); 0.26-0.64), 86.67% (95% CI; 0.76-0.93), 56.52% (95% CI; 0.34-0.76) and 80.25% (95%CI; 0.69-0.88). Positive likelihood ratio and negative likelihood ratio of HSG in detecting uterine cavity abnormality was 3.36 and 0.64 respectively. The agreement between HSG and hysteroscopy was 75%. This was statistically significant (P value = 0.001) with fair strength of agreement between HSG and hysteroscopy. (k value= 0.336). Conclusion: Hysteroscopy should be performed in all infertile patients as it can detect significant number of incidental findings missed by HSG.